2023
DOI: 10.3390/jcm12072636
|View full text |Cite
|
Sign up to set email alerts
|

Updated Immunotherapy for Gastric Cancer

Abstract: Gastric cancer treatments are evolving rapidly. For example, immune checkpoint inhibitors, especially those that target PD-1 or PD-L1, have long-term efficacy in a subset of gastric cancer patients, and are currently the first-line therapy. Immunotherapies approved for use in untreated gastric cancer patients include monotherapy and chemotherapy-immunotherapy combinations. Major clinical trials have reported efficacy and safety data suggesting that PD-L1 expression is important for regimen selection, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…While immune checkpoint inhibitor (ICI)-based immunotherapy has emerged as a promising treatment for late-stage GC patients, its effectiveness can be hindered by immunosuppressive cell subsets within TME. 35 As the above-mentioned data indicated the immunosuppressive role of CPT1C + CAFs by promoting M2-like phenotype of macrophages via heightened secretion of IL-6, we hereby investigated the potential association between CPT1C + CAFs infiltration and patient response to immunotherapy ( Figure 5(d) ). In fact, it was noted in KIM immunotherapy cohort that GC patients in the high CPT1C + CAFs group exhibited significantly lower response rate to immunotherapy compared to those with low CPT1C + CAFs ( Figure 5(e) ), and CPT1C + CAF infiltration level of immunotherapy responders was remarkably lower than non-responders ( Figure 5(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…While immune checkpoint inhibitor (ICI)-based immunotherapy has emerged as a promising treatment for late-stage GC patients, its effectiveness can be hindered by immunosuppressive cell subsets within TME. 35 As the above-mentioned data indicated the immunosuppressive role of CPT1C + CAFs by promoting M2-like phenotype of macrophages via heightened secretion of IL-6, we hereby investigated the potential association between CPT1C + CAFs infiltration and patient response to immunotherapy ( Figure 5(d) ). In fact, it was noted in KIM immunotherapy cohort that GC patients in the high CPT1C + CAFs group exhibited significantly lower response rate to immunotherapy compared to those with low CPT1C + CAFs ( Figure 5(e) ), and CPT1C + CAF infiltration level of immunotherapy responders was remarkably lower than non-responders ( Figure 5(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, owing to unconfirmed clinical benefits, pembrolizumab has been withdrawn as a third-line treatment for GC [ 25 ]. Some biomarkers such as EBV infection, MSI, TMB, and PD-L1 expression have been found to predict immunotherapy efficacy, while studies have reported inconsistent results [ 4 ]. There is still a need to further improve the prediction of immunotherapy response, especially in the second/third-line treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the first-line treatment of metastatic HER2-negative GC, pivotal phase III trials, such as CheckMate 649, KEYNOTE-859, and ORIENT-16, reported that the combination of ICIs with chemotherapy significantly improved overall survival (OS) and progression-free survival (PFS) compared with chemotherapy alone [ 2 ]. However, in both the CheckMate 649 [ 3 ] and ORIENT-16 trials [ 4 ], the survival benefit of immunotherapy seems to come mainly from patients with PD-L1 combined positive score (CPS) ≥ 5, whose proportions (60 and 61%, respectively) were substantially higher than other reports, and such benefit is still controversial in patients with CPS < 5 [ 5 ]. In addition, immunotherapy in second/third-line therapies of GC still has a very limited efficacy (approximately 10% for monotherapy response), regardless of PD-L1 expression [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that trastuzumab therapy may upregulate PD-1 and PD-L1 expression and that, conversely, ICIs may improve the therapeutic efficacy of anti-HER2 agents [ 12 ]. Based on these results, phase I and II clinical trials have shown the treatment efficacy of trastuzumab and ICIs in combination with CT in HER2-positive GA/GEJA [ 15 ]. Since May 2021, the Food and Drug Administration (FDA) granted the accelerated approval for the addition of pembrolizumab to trastuzumab and CT (with platinum and fluoropyrimidine) in locally advanced unresectable or metastatic HER2-positive GA/GEJA [ 2 , 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%